EKSISTENSI KIAI DALAM MASYARAKAT - Sayfa Auliya Achidsti (IBDA` : Jurnal Kajian Islam dan Budaya, 2014)
Kiai as a social actor, who closely related to religion, has double entities, as a kiai himself and as a Muslim. The first concept is usually apllied in netral discussion on viewing a scholar and the activity of kiai for his followers, how he do preach (dakwah), methods, and other discussions that relate to the influenced power of kiai in his society. The second study is how kiai preaching, the way and methods and other studies like how is kiai power toward the society. The next study is about the kiai’s preach, methods and ways related to how the existence of kiai is build. The capital of kiai figure, finally can be seen as a consequence from good Muslim, and people in the society tend to acquire it.